2014
DOI: 10.1007/s00432-014-1742-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different rabbit ATG preparation effects on early lymphocyte subset recovery after allogeneic HSCT and its association with EBV-mediated PTLD

Abstract: We conclude that high, but importantly not currently applied low dosages of ATG-G, impair thymic T cell regeneration and memory T cell immunity to a greater extent than ATG-F in pediatric patients. In addition, our results suggest an increased risk for EBV-PTLD when treated with ATG-G. Prospective studies are warranted to compare different ATG preparations with regard to the immune reconstitution and EBV-PTLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Patients receiving 15 mg/kg ATG showed a delay of CD19+ cells, but also of CD3+ and CD4+ cells compared to patients receiving ATG at a dosage of 7.5 mg/kg. A recently published study in pediatric patients comparing the influence on immune reconstitution of ATG-G (Thymoglobuline) and ATG-F (Fresenius) found decreased B-cell numbers at day 100 post-transplantation with no significant differences between the 2 ATG preparations (31). The decreased numbers of transitional and na€ ıve B cells at days 15 and 30 may seem to also be related to the B cell activity of ATG-F, as the rabbit IgG persists for more than 100 days after transplantation and correlates with pregraft doses (32).…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving 15 mg/kg ATG showed a delay of CD19+ cells, but also of CD3+ and CD4+ cells compared to patients receiving ATG at a dosage of 7.5 mg/kg. A recently published study in pediatric patients comparing the influence on immune reconstitution of ATG-G (Thymoglobuline) and ATG-F (Fresenius) found decreased B-cell numbers at day 100 post-transplantation with no significant differences between the 2 ATG preparations (31). The decreased numbers of transitional and na€ ıve B cells at days 15 and 30 may seem to also be related to the B cell activity of ATG-F, as the rabbit IgG persists for more than 100 days after transplantation and correlates with pregraft doses (32).…”
Section: Discussionmentioning
confidence: 99%
“…In 1 Thymo trial [21], 33.0% of the patients in the ATG arm had Epstein-Barr virus reactivation, compared with 3.0% in the non-ATG arm, whereas these rates were similar in 1 ATLG trial (3.6% compared with 1.4%) [20]. A specifically designed trial with adequate numbers of patients is needed to resolve these controversial questions [27]. The evidence synthesized in this NMA is supported using HR in most efficacy endpoints as an effect measure, which is assumed to suffer somewhat less from selection bias than RR with respect to the endpoints chosen and can indicate risks occurring before the endpoint [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown by Höcker et al that VGC in EBV high risk patients (D+/R-) is reducing the incidence of EBV primary infection and in case of primary infection patients with VGC have significant lower EBV viral load [18]. Early EBV reactivation after ATGs is widely described in patients after induction treatment for bone marrow transplantation [19;20]. Mensen et al found a similar incidence of EBV-reactivation in patients who received ATG-F or Thymo for induction treatment for allogenic bone marrow transplantation but significant higher copies in patients who received Thymo.…”
Section: Discussionmentioning
confidence: 99%